Pola Pendidikan Agama Islam pada Keluarga Petani di Desa Batu Nampar Kecamatan Jerowaru: Islamic Religious Education Patterns in Farming Families in Batu Nampar Village, Jerowaru District - Muhamad Zaril Gapari (Al-Faiza : Journal of Islamic Education Studies, 2026)
The purpose of this study was to determine the Islamic Religious Education Pattern used by parents in educating their children in the farming family environment in Batu Nampar Village, Jerowaru District. This study used qualitative methods using interview, observation and documentation methods. The results of the study indicate that the implementation of Islamic Religious Education for children in farming families begins from early childhood and is carried out in each family environment through daily life, in the mosque or in the prayer room and in the TPQ. Farming families in educating Islam in the family environment, use the method of habituation, role model and advice method which are the most appropriate educational methods in the family environment. The Educational Pattern used by farming families in Batu Nampar Village, Jerowaru District in educating their children about Islam in the family environment consists of educational patterns that have an Authoritative tendency, an Authoritarian educational pattern, and an educational pattern that has a permissive tendency.